P36 Injections of intravenous contrast for computerised tomography scans precipitate migraines in hereditary haemorrhagic telangiectasia subjects at risk of paradoxical emboli: implications for right-to-left shunt risks. (15th November 2016) - Patel, T; Elphick, A; Jackson, JE; Shovlin, CL
Abstract : Introduction and objectives: Migraine headaches commonly affect people with pulmonary arteriovenous malformations (PAVMs) that provide right-to-left shunts. The majority of PAVMs are due to underlying hereditary haemorrhagic telangiectasia (HHT). In our clinical practice, patients occasionally reported acute precipitation of migraine headaches following injection of technetium-labelled albumin macroaggregates for nuclear medicine scans. Our goal was to evaluate if injection of intravenous particles may provoke migraines in the cohort. Methods: Self-reported migraine features and exacerbations were examined in HHT subjects with and without pulmonary AVMs, for a series of noninvasive and invasive investigations, using an unbiased online survey. With ethical approval, the study recruited between August 2013–April 2015. Data were downloaded in December 2015 for analysis using STATA IC v12 and GraphPad Prism. Two group comparisons were performed using Mann Whitney or Fisher's exact test (for proportions). Multiple groups were compared using Kruskal Wallis with Dunn's multiple comparison test. Results: 166 subjects were classified as having both HHT and migraines. HHT subjects with migraines were more likely to have pulmonary AVMs (p < 0.0001). Pulse oximetry, x-rays, ultrasound and computerised tomography (CT) scans without intravenous contrast medium rarely, if ever, provoked migraines, but unenhanced magnetic resonance imaging (MRI) was reported to exacerbate migraines by 14/124 (11.2%) subjects. 114 had both enhanced and unenhanced CT examinations: studies with contrast media were more commonly reported to start (9/114 [7.8%]), and/or worsen migraines (18/114 [15.7%]) compared to those undertaken without contrast medium (p < 0.01), or after simple blood tests (p < 0.05). Additionally, migraine exacerbation was reported by 9/90 (10%) after contrast echocardiography, 2/44 (4.5%) after nuclear medicine scans, and 10/154 (6.5%) after blood tests. Conclusions: In this population, MRI studies, blood tests, contrast echocardiograms, and intravenous injection of iodinated contrast medium associated with CT examinations were reported to provoke or exacerbate migraines. Since air emboli are recognised to complicate intravenous injections, particularly following pressurised pump injections of CT scan contrast, evaluation of migraines as a potential read-out for paradoxical emboli is recommended. In the meantime, for people with HHT and migraines, pre-test counselling may helpfully include advice to bring migraine preventers or treatments to help alleviate symptoms promptly.